2010
DOI: 10.1016/j.virusres.2010.07.029
|View full text |Cite
|
Sign up to set email alerts
|

The structural biology of PRRSV

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an enveloped, positive-sense single-stranded RNA virus belonging to the Arteriviridae family. Arteriviruses and coronaviruses are grouped together in the order Nidovirales, based on similarities in genome organization and expression strategy. Over the past decade, crystal structures of several viral proteins, electron microscopic studies of the virion, as well as biochemical and in vivo studies on protein-protein interactions have led to a greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
185
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(209 citation statements)
references
References 134 publications
(209 reference statements)
1
185
0
3
Order By: Relevance
“…Transmembrane regions were also predicted using the TMHMM server (http://www.cbs. dtu.dk/services/TMHMM/), and two transmembrane regions were identified on the basis of our prediction results and previous report [31]. Models to reveal the interaction between the structural proteins were constructed based on reports [31,32] and our findings (Figure 6(a)) and the topological alteration of GP3 was constructed as shown in Figure 6(b) and (c).…”
Section: Topological Analysis Of Wild Type Gp3 and Mutated Gp3mentioning
confidence: 87%
See 2 more Smart Citations
“…Transmembrane regions were also predicted using the TMHMM server (http://www.cbs. dtu.dk/services/TMHMM/), and two transmembrane regions were identified on the basis of our prediction results and previous report [31]. Models to reveal the interaction between the structural proteins were constructed based on reports [31,32] and our findings (Figure 6(a)) and the topological alteration of GP3 was constructed as shown in Figure 6(b) and (c).…”
Section: Topological Analysis Of Wild Type Gp3 and Mutated Gp3mentioning
confidence: 87%
“…dtu.dk/services/TMHMM/), and two transmembrane regions were identified on the basis of our prediction results and previous report [31]. Models to reveal the interaction between the structural proteins were constructed based on reports [31,32] and our findings (Figure 6(a)) and the topological alteration of GP3 was constructed as shown in Figure 6(b) and (c). For wild type GP3, the secondary structure prediction showed that 106 aa out of 254 aa in GP3 formed coils in the structure, which indicated that GP3 might be very flexible especially in ectodomain of the protein.…”
Section: Topological Analysis Of Wild Type Gp3 and Mutated Gp3mentioning
confidence: 87%
See 1 more Smart Citation
“…The nucleocapsid protein (N) is encoded by ORF7. N is the major structural element within the PRRSV virion and forms disulfide-linked homodimers; It functions to package the viral genomic RNA and is the only known structural protein, which does not encode a transmembrane domain (Dokland, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ORF1a와 ORF1b는 바이러스 복제와 전사에 필요한 14개의 비구조단백질을 coding한다 (Dokland, 2010). 피막을 가지고 있는 바이러스 입자 에는 3개의 중요한 단백, 즉 glycosylated envelope protein (GP5, 25 kDa), unglycosylated membrane protein (M, 18 kDa), 그리고 nucleocapsid protein (N, 15 kDa)…”
unclassified